2019
DOI: 10.1007/s40093-019-0260-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium chloride extracted from eggshell in maintaining quality of selected fresh-cut fruits

Abstract: Purpose A study was conducted to extract calcium chloride from eggshell and also to check the effect of commercially available and extracted calcium chloride on quality characteristics of fresh-cut fruits. Methods Eggshells were mixed with a hydrochloric acid solution and stirred occasionally until no gas bubbles were observed (3 h). The mixture was centrifuged at 3500 rpm for 10 min at 4 °C, the supernatant was separated and heated to 110-115 °C until dried, this yielded calcium chloride crystals or eggshell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
(19 reference statements)
2
17
0
Order By: Relevance
“…The incorporation of CaCl2 resulted in less of a decrease in the pH value. These results are aligned with the findings from Thakur's group, which investigated the effects of CaCl2 solution on fresh-cut fruits, and reported that the fruits immersed in CaCl2 solution exhibited higher pH value compared to the non-treated fruits [8]. The explanation…”
Section: Physicochemical Analysis and Colorimetry Of The Fresh-cut Apple Slicessupporting
confidence: 89%
See 4 more Smart Citations
“…The incorporation of CaCl2 resulted in less of a decrease in the pH value. These results are aligned with the findings from Thakur's group, which investigated the effects of CaCl2 solution on fresh-cut fruits, and reported that the fruits immersed in CaCl2 solution exhibited higher pH value compared to the non-treated fruits [8]. The explanation…”
Section: Physicochemical Analysis and Colorimetry Of The Fresh-cut Apple Slicessupporting
confidence: 89%
“…The incorporation of CaCl 2 resulted in less of a decrease in the pH value. These results are aligned with the findings from Thakur's group, which investigated the effects of CaCl 2 solution on fresh-cut fruits, and reported that the fruits immersed in CaCl 2 solution exhibited higher pH value compared to the non-treated fruits [8]. The explanation could be that the reduction of pH value is related to the organic acid generated by microorganisms, and the embedded CaCl 2 inhibited the growth of microorganisms, thus resulting in a higher pH value.…”
Section: Physicochemical Analysis and Colorimetry Of The Fresh-cut Apple Slicessupporting
confidence: 88%
See 3 more Smart Citations